The effect of counseling on hemoglobin on the knowledge of Islamic boarding school students - Chalies Diah Pratiwi; Andyanita Hanif Hermawati; Nosa Ika Cahyariza (Journal of Community Service and Empowerment, 2023)
Anemia is a condition where the mass of erythrocytes or hemoglobin in circulation cannot fulfill its function to provide oxygen to body tissues. Anemia in adolescent girls is still quite high; the world prevalence of anemia ranges from 40 to 88%. Community service activities aim to screen (check) hemoglobin levels as early detection of anemia using the Point of Care Testing (POCT) method to determine the relationship between age and education to the incidence of anemia and as a preventive effort to minimize anemia. This activity was carried out through counseling about hemoglobin using the lecture method at the Islamic Boarding School Roudlotul Musthofa in May with 23 female students as respondents, which were then analyzed using the Wilcoxon statistical test. The results of the questionnaire before counseling (pre-test) obtained an average of 80, then counseling was carried out, and the average results of the questionnaire (post-test) were 94. The results of the Wilcoxon Test analysis showed p (Asymp.Sig. (2-tailed)) = 0.000 < α (0.05), which means that there is a significant influence between the knowledge of junior high school students of Raudlatul Mustofa Islamic Boarding School Tulungagung Regency and hemoglobin counseling conducted.